Understanding Muslim women entrepreneurial success - Chong, Chin Wei (Advances in business related scientific research journal, 2026)
Women's entrepreneurship is vital for the development of MSMEs in Malaysia, as it contributes significantly to the country’s economy and the employment rate. It therefore attempts to identify the influence of personal and external factors on the entrepreneurial success of Muslim women entrepreneurs in Malaysia. Specifically, within the culturally and religiously sensitive context, nine elements, which include need for achievement, risktaking, innovativeness, education, government support, access to finance, perceived social support, networking, and social culture, are explored to seek their effects on Muslim women’s entrepreneurial outcomes. For this research, a total of 150 Muslim women entrepreneurs operating micro and small enterprises in Klang Valley, Selangor, were surveyed. The SmartPLS 4 software package was used to analyze the structural hypotheses in the study. Surprisingly, this research affirms that only risk-taking and networking are found to be significantly related to Muslim women entrepreneurs’ entrepreneurial success. Overall, this study contributes to the limited body of empirical research focused on this underserved group by integrating internal and external factors within an Islamic cultural framework. It also provides implications for policymakers, government agencies, and support institutions as they design culturally relevant Muslim women entrepreneurship programs, improve networking opportunities, and cultivate peer collaboration among them.
Keywords: entrepreneurial success; Malaysia; micro and small enterprises; Muslim women entrepreneurs; women empowerment